Naphthalene and 2,3-dihydrobenzo[b][1,4]dioxine derivatives with extended side chains as new scaffolds of CB2-selective ligands - Osman, Noha; Mahmoud, Amr H.; Klein, Christian D.; Allarà, Marco; Marzo, Vincenzo Di; Abouzid, Khaled M.; Abadi, Ashraf H. (MedChemComm, 2014)
Herein, we report the synthesis of naphthalene, dihydrobenzodioxine and fluorene derivatives with extended side chains and their biological evaluation as ligands of CB1 and CB2 receptors. Compounds 6a and 18b showed Ki values in the submicromolar range and relatively high selectivity toward CB2. Active compounds represent new scaffolds with such type of activity. Moreover, a multiple XED-based field templates model has been constructed for the activity interpretation of some of the synthesised compounds. The reported ligands can serve as a template to develop new CB2 ligands with enhanced potency and selectivity, and the computational model can be applied for SAR interpretation and/or structure optimization of any other CB2-selective ligand(s).
Im Titel ist "2" in CB2 tiefgestellt
Gesehen am 20.07.2020